Chronic cough: a herald symptom of thoracic aortic aneurysm in a patient with a bicuspid aortic valve. (1st September 2014) - Miller, Charles Philip; Firoozan, Soroosh; Woo, Eric K; Apps, Andrew
Abstract : Chronic cough has a wide differential, of which thoracic aortic aneurysm is a rare but potentially devastating cause. We present a patient with previous aortic valve replacement for a bicuspid valve who had been suffering from a chronic cough for 8 months and who developed subsequent voice hoarseness. This had been initially managed in the community with trials of steroid inhalers, steroid nasal sprays and proton pump inhibitors to no avail. He was referred to cardiology and chest clinics. An urgent CT aortogram was requested given his widened mediastinum on chest radiograph, cardiac history of bicuspid valve and symptoms. This revealed a large aneurysm of the thoracic aorta with chronic dissection that required urgent operative intervention. His cough resolved 6 weeks postoperatively. The purpose of this report is to highlight thoracic aortic aneurysms as a potential rare differential for chronic cough and as a complication of patients with bicuspid aortic valves.